Design and Implementation of a Transistorized Bi-Controlled based Utility-Connected Battery Charger for Underdeveloped Nations - Jagun, Z.; Okandeji, A.; Eya, C.; Olajide, M.; Ominike, A.; Ukagu, S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
This paper presents a transistorized bi-controlled based utility-connected battery charger to address the problem of erratic public power supply in underdeveloped nations. In this study, a utility battery charger was built by the integration of grid power supply, line frequency transformer, power electronic switches, alternating current-direct current bridge converter, regulator, and resistor-inductor-capacitor. The excess-voltage protection and battery monitoring were obtained by the bi-controlled technique. In contrast to other charging systems in underdeveloped nations, the proposed system is very simple, rugged, reliable and cheap to maintain due to simplicity and un-programmed nature of the system. The results showed that the proposed system is craggy and robust to resist voltage stress, highly reliable and relatively free from leakage currents due to the presence of a double controlled scheme using a common point of action and a line frequency transformer. In addition, the system can be used to charge batteries ranging from 50µA and above. The system can be utilized in communication companies, electric vehicles, drilling machines.